Identifying the functional groups and the influence of synthetic chelators on Cd availability and microbial biomass carbon in Cd-contaminated soil. Issue 2 (28th January 2018) - Chhajro, Muhammad Afzal; Fu, Qingling; Shaaban, Muhammad; Rizwan, Muhammad Shahid; Jun, Zhu; Salam, Abdus; Kubar, Kashif Ali; Bashir, Saqib; Hongqing, Hu; Jamro, Ghulam Murtaza
ABSTRACT: Synthetic chelators play an important role in boosting the microbial biomass carbon (MBC), dissolved organic carbon (DOC), and heavy metal solubility in a contaminated soil toward a sustainability of environment for agricultural crops. Castor plant was grown under different levels of Cd contaminated soil (−Cd and +Cd) following adding three chelating agents, ethylenediaminetetraacetic acid (H4 EDTA), nitriloacetic acid (H3 NTA), and NH4 citrate (ammonium citrate) to the soil at rates of 10, 15, and 25 mmol in 5 kg of soil per pot. The highest bioavailable Cd concentrations in soil and castor plant were obtained from NH4 citrate and H4 EDTA treatments in the contaminated soil. Fourier transform infrared (FTIR) analysis showed that NH4 citrate was the most effective chelator in Cd-contaminated soil. MBC and DOC contents were significantly increased and reached at 81.98–80.37 and 1.96–1.90 mg kg −1 respectively, in the (H3 NTA) and NH4 citrate treatments in Cd-contaminated soil. Further research is needed to investigate the use of chelators in the phytoextraction of Cd-contaminated soils under field conditions and whether it may be beneficial in accelerating the phytoextraction of Cd through hyperaccumulating plants.